ANALISIS FAKTOR-FAKTOR PENGUNGKAPAN INTELLECTUAL CAPITAL (PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI TAHUN 2011-2017) - febrian, Yudha (Pascasarjana Universitas Sultan Ageng Tirtayas, 2019)
The research of this thesis is entitled analysis of determinants of intellectual capital disclosure in Pharmaceutical Companies listed on the Indonesia Stock Exchange in 2011-2017. The purpose of this study was to determine the effect of the audit committee size, the independence of the audit committee, the number of financial experts in the audit committee, the number of audit committee meetings, the size of the board of commissioners, the independence of the board of commissioners, the number of board of commissioner meetings and institutional ownership of disclosure of pharmaceutical companies' intellectual capital. The research population is pharmaceutical companies listed on the Stock Exchange for the period 2011-2017. The research sample consisted of 11 pharmaceutical companies with 7 years of observation. Sample data are 77 financial report data. The research method uses quantitative methods. The research design consisted of descriptive design and causal design. Data analysis using Multiple Linear Regression Analysis using SPSS Version 20. statistical program. Based on the results of data processing, it is known that the Adjusted R Square value is 0.462. This shows that variations in the Intellectual Capital Disclosure variable can be explained by 46.2% by Audit Committee Size variables, Audit Committee Independence, Number of Audit Committee Financial Experts, Number of Audit Committee Meetings, Board of Commissioners Size, Board of Commissioners Independence, Number of Board of Commissioners Meetings , Institutional ownership and company size as control variables while the remainder is explained by other variables not examined. The results of testing the hypothesis, it is known that the size of the audit committee, the independence of the audit committee, the number of audit committee financial experts, the size of the board of commissioners and the independence of the board of commissioners have a positive effect on disclosure of intellectual capital Audit committee meetings have no effect on disclosure of intellectual capital.